Systematic Review of Different Reperfusion Therapy Methods in Patients with ST-Elevation Acute Coronary Syndrome: Literature Review (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. Systematic analysis and comparison of different reperfusion therapy methods in patients with ST-elevation acute coronary syndrome (STEMI), including primary percutaneous coronary intervention (pPCI) and thrombolytic therapy (TLT), with emphasis on time factor and COVID-19 pandemic impact. Materials and methods. A systematic review of prospective randomized and observational studies comparing pPCI and TLT effectiveness in STEMI patients was conducted. Data from major international trials including DANAMI-2 (1572 patients), PRAGUE-2, STAT, GISSI, ISACS-STEMI COVID-19, meta-analyses of 23 studies, and modern global longitudinal strain assessment methods were analyzed. Results. Meta-analysis of 23 randomized studies showed statistically significant pPCI advantages over TLT: 30-day mortality 8.0% vs 13.7% (p=0.0003), recurrent infarction 3.8% vs 7.0% (p<0.05), revascularization need 5.7% vs 25.2% (p<0.001). "Golden hour" concept was confirmed. COVID-19 pandemic led to 19-30.5% reduction in STEMI presentations and worse prognosis. Conclusion. pPCI demonstrates statistically significant advantages over TLT, however method selection should consider time factor and technical availability. Modern global longitudinal strain assessment methods improve prognostic accuracy.